2020
DOI: 10.35484/pssr.2020(4-i)27
|View full text |Cite
|
Sign up to set email alerts
|

DREEM Inventory: Investigating Learning Environment of Pre-Service Teacher Education Programs

Abstract: Keeping in view the significance of learning environment of the academic institutions, this study was designed to explore the perceptions of students regarding the learning environment in the departments of teacher education of general universities in Punjab, Pakistan. The population of the study was comprised of students enrolled in 8 th Semester of bachelor programs. Cluster sampling technique was applied to select the sample N=218. A standardized tool Dundee Ready Education Environment Measure (DREEM) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…On the contrary availability of proper resources for e-learning has remained a major concern for the educators in previous studies. 16,17 Similarly according to mean values, educators at Sahiwal Medical College Sahiwal found video recording more comfortable than conventional lectures delivery in lectures halls which is also contrary to a previous study. 18 This fact was also supported in answering to a question related to difficulty of teaching via e-learning, mean value was lesser in this regard.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…On the contrary availability of proper resources for e-learning has remained a major concern for the educators in previous studies. 16,17 Similarly according to mean values, educators at Sahiwal Medical College Sahiwal found video recording more comfortable than conventional lectures delivery in lectures halls which is also contrary to a previous study. 18 This fact was also supported in answering to a question related to difficulty of teaching via e-learning, mean value was lesser in this regard.…”
Section: Discussioncontrasting
confidence: 59%
“…Studies previously found factors other than motivation got better response from the teachers. 17 Able to prepare students better with the help of e-learning and the availability of the materials for the e-learning methods also got good mean scores from the faculty of Sahiwal Medical College Sahiwal. On the contrary availability of proper resources for e-learning has remained a major concern for the educators in previous studies.…”
Section: Discussionmentioning
confidence: 99%